Efect of the storage on postharvest quality and antioxidant capacity of Syzygium paniculatum Gaerth - Pote Ordoñez, Dayana de los Ángeles (2025)
The Magenta tree (Syzygium paniculatum Gaertn), native to Australia, has been introduced and cultivated in several areas of Ecuador. Commonly known as Eugenia Fruit, it is primarily an ornamental plant. In Australia, this species is threatened or vulnerable. It produces medium-sized, round, brightly colored fruits with a sweet, refreshing flavor. Despite being edible, its consumption is rare due to a lack of knowledge about its characteristics. It is cultivated primarily for its decorative value in gardens and landscapes, appreciated for its lush foliage. This study evaluates the effect of different storage treatments (20°C and 7°C, 0 and 15 days) on the physicochemical properties and antioxidant capacity of Syzygium paniculatum. Parameters such as color, size, fresh weight, diameter, seed weight, edible portion, acidity, and pH were analyzed, as well as general characteristics and chemical composition (humidity AOAC 934.05; ash AOAC 940.26; protein by Kjeldahl method AOAC 920.152; fat AOAC 948.22; fiber AOAC 945.38; carbohydrates by calculation). During storage, weight loss, respiration rate, and antioxidant activity of the fruit were investigated. The purpose is to provide relevant information to optimize storage practices, preserving the nutritional, functional, and visual quality of the fruits, and thus maximize their potential as a functional food or ingredient in various food industries.